Talent Management Practices and Employee Performance in the Nepalese Banking Sector: The Mediating Role of Employee Engagement - Prajapati, Nabin; Lama, Puja (Bagiswori Journal, 2026)
This study aims to examine the influence of talent management on employee performance with employee engagement serving as a mediating variable in commercial banks of Nepal. The research adopted causal comparative research design. Data were collected through structured questionnaires distributed to 300 employees selected using purposive sampling with the criterion of having at least one year of work experience and employees working in private, public and joint venture bank. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that talent management has a significant positive effect on employee performance, both directly and indirectly through employee engagement. These results indicate that the integrated implementation of talent management, employee engagement plays a vital role in enhancing employee performance. This study provides valuable practical implications for organizations seeking to improve performance through strategic human resource management practices.